We Wish to Inform You that Tomorrow We Will be Killed With our Families : Stories from Rwanda - Gourevitch, Philip 1961- (London Picador, 1999)
A Tutsi pastor, in a letter to his church president, used the chilling phrase that gives this book its title
Includes Maps
Originally published: New York: Farrar, Straus & Giroux, 1998
Keywords: Rwanda -- Ethnic relations -- Genocide